PENGARUH METODE SOCRATIC BERBANTUAN MEDIA ROLLING BALL GAMES TERHADAP HASIL BELAJAR MATEMATIKA KELAS V SDN 14 SINGKAWANG - Dela; Istirahayu, Iip; Guna Utama, Erdi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low achievement of Mathematics learning outcomes of fifth grade students at SDN 14 Singkawang.This study aims to identify the influence, magnitude of influence, and analyze the implementation of the socratic method assisted by rolling ball games media on the mathematics learning outcomes of fifth-grade students of SDN 14 Singkawang. This study uses a quantitative approach with a pre-experimental one group pretest-posttest design. The study population was 28 students, with a saturated sampling technique so that the entire population was sampled. Data collection techniques included tests and non-tests using learning outcome question instruments and learning implementation observation sheets. The prerequisite test was carried out using the Shapiro-Wilk normality test, while the hypothesis test used the Paired Samples T-Test. The results showed a significant effect of the application of the socratic method assisted by rolling ball games media on students' mathematics learning outcomes, with a significance value of 0.001 <0.05. The magnitude of the effect obtained based on the Cohen's d effect size calculation of 1.317 is included in the large category. In addition, the implementation of learning is in the very good category with a percentage of 88%. Thus, the application of the Socratic method assisted by rolling ball games media is effective and significant in improving the mathematics learning outcomes of fifth grade students at SDN 14 Singkawang.